Irrigation-induced Salinization Effects on Soil Chemical and Biological Properties under Cotton-Wheat Rotation on Loamy Sand Soil in Northwest India - and M.S. Mavi, Pawitar Singh, O.P. Choudhary (Journal of the Indian Society of Soil Science, 2019)
Secondary soil salinilization is a major problem in irrigated agriculture. We studied the effects of irrigation-induced salinity on soil biological and chemical properties under cotton-wheat rotation at experimental farm, Punjab Agricultural University, Ludhiana, India. Sixty fresh soil samples were collected from 0-15 cm and 15-30 cm soil depth irrigated with different levels of saline water (EC 0, EC 3, EC 6, EC 9 and EC 12 dS m-1). The soil samples were analyzed for soil chemical properties (pH, EC, SAR, soluble ions (Na+, K+, Ca2+ + Mg2+ and Cl-), soil fertility parameters (organic C, available N and P) and biological properties namely, microbial biomass carbon (MBC), microbial biomass nitrogen (MBN), dehydrogenase activity (DHA) and cold water extractable carbon (CWEC). Increasing salinity of irrigation water significantly increased soil pH, EC, SAR, soluble Na+ and Cl- content and decreased organic C, N and P content at two soil depths. At highest salinity level, (EC 12 dS m-1), DHA, MBC and CWEC decreased by 54.8, 52.9 and 45.6 per cent and MBN by 70 per cent compared to control at 0-15 cm soil depth. The results revealed that similar trend was observed in case of 15-30 cm soil depth for all biological properties but percentage decrease was more over control at highest salinity level of irrigation water. It may be concluded that at higher salinity levels (EC 9 and 12 dS m-1), soil chemical and biological properties were more affected compared to low salinity levels.